High fidelity two-qubit gates on fluxoniums using a tunable coupler - Ilya N. Moskalenko; Ilya A. Simakov; Nikolay N. Abramov; Alexander A. Grigorev; Dmitry O. Moskalev; Anastasiya A. Pishchimova; Nikita S. Smirnov; Evgeniy V. Zikiy; Ilya A. Rodionov; Ilya S. Besedin (npj Quantum Information, 2022)
Abstract Superconducting fluxonium qubits provide a promising alternative to transmons on the path toward large-scale superconductor-based quantum computing due to their better coherence and larger anharmonicity. A major challenge for multi-qubit fluxonium devices is the experimental demonstration of a scalable crosstalk-free multi-qubit architecture with high-fidelity single-qubit and two-qubit gates, single-shot readout, and state initialization. Here, we present a two-qubit fluxonium-based quantum processor with a tunable coupler element. We experimentally demonstrate fSim-type and controlled-Z-gates with 99.55 and 99.23% fidelities, respectively. The residual ZZ interaction is suppressed down to the few kHz levels. Using a galvanically coupled flux control line, we implement high-fidelity single-qubit gates and ground state initialization with a single arbitrary waveform generator channel per qubit.